STRUCTURAL ORGANIZATION OF THE HUMAN SPINAL CORD FETUSES 39-40 WEEKS PRENATAL PERIOD - Shkolnikov, V.S. (World of Medicine and Biology, 2015)
Spinal cord - an important center for the regulation of the internal organs and the body, which has several patterns of development and structure, as in phylo and in ontogenesis. However, the subject of debate left radial glial role in the processes of differentiation of neurons and glia cells, was described morphology neuroepithelium, and no systematic description of structures histogenesis spinal cord segments. Material and methods: An anatomical and histological examination of the spinal cord 18 human fetuses gestational period of 39-40 weeks using immunohistochemistry methods. Results: Obtained the following linear morphometric parameters spinal cord segments: transverse dimension at the cervical thickening - 7,4 ± 0,2 mm anteroposterior size - 4,8 ± 0,2 mm; transverse dimension at the level of the thoracic segments - 4,3 ± 0,1 mm anteroposterior size - 3,6 ± 0,1 mm; transverse dimension at the lumbosacral thickening - 6,4 ± 0,2 mm anteroposterior size - 5,1 ± 0,2 mm; transverse dimension at the level of the sacral segments - 3,9 ± 0,2 mm anteroposterior size - 3,2 ± 0,1 mm. Its area of gray matter at the level of the cervical thickening - 11,8 ± 0,4 mm 2, the thoracic segments - 5,4 ± 0,2 mm2 at the lumbosacral thickening - 12,9 ± 0,5 mm2 and at the sacral segments - 4,7 ± 0,2 mm2. Its area of white matter of the spinal cord at the cervical thickening - 18,1 ± 0,8 mm2, the thoracic segments - 7,3 ± 0,3 mm2 at the lumbosacral thickening - 12,5 ± 0,5 mm2 segments - 3,0 ± 0,1 mm2. The degree of differentiation of motor neurons predominate, then - false (sensitive) and relatively smallest degree of differentiation with autonomic neurons. Principle histostructure neyroepitelialnoho same layer in all segments of the spinal cord. It consists of ependymnyh cells ellipse shape, located on the basement membrane. The average area of cells that form neuroepitelium is 42,3 ± 1,4 um2. Among ependymal cells in subependymal area, meet single spherical cells with an area average is 26,8 ± 0,6 um2. Such cells expressing Ki-67, but the expression of Ki-67 is weak and is patchy, mainly in the ventral part of the neuroepithelium. The relatively high expression of vimentin observed in radial glia remains around the central canal and along the posterior median septum. In the mantle layer weak expression of vimentin observed in vessel walls and mediocre vimentin expression in the white matter. In a strong expression of S-100 in glial cells, the expression of S-100 is also in neurons of the spinal cord. The relatively strong expression was observed synaptophisin us within neural systems anterior horn and mediocre expression within the posterior horns. Conclusions: As a result of complex anatomical and histological study we established morphometric parameters tsytoarhitektonichni particular structure of spinal cord segments of human fetuses 39-40 weeks. intrauterine period of development and morphology neuroepithelium and features of NSC proliferation.